An Innovative Method For Prevention Of Episodoic Emergencies - Testing Of A New Allergic Method For The Diagnostic Of Animal Brucelliosis - Ulugmuradov A.D; Turdikulov A.A.; Adilov S.A. (Zien Journals, 2023)
This article provides information on the research conducted in the conditions of Uzbekistan on allergy diagnostics, which is one of the new innovative methods for diagnosing brucellosis in small cattle, in particular, materials are given on the development of the production of allergens from brucella stored in a unique collection of animal microorganisms Veterinary Scientific Research Institute.
Keywords: collection; brucella; unique; materials